Promoting payments for ecosystem services in the danube region: theoretical-methodological bases and practical measures - Rubel, O. (Економічні інновації, 2012)
Specification and generalizations of theoretical-methodological bases of
development of payment for ecosystems services mechanisms on their
introduction in economics of Danube region are presented. Узагальнено теоретико-методологічні основи впровадження механізмів плати за екосистемні послуги та представлено конкретні шляхи по їхньому просуванню в економічну практику Дунайського регіону.